DARI TRADISI KE TRENDING: EKSPRESI BUDAYA DAN KAPITALISASI DI PLATFORM LIVE TIKTOK - Az-Zahra, Andi Nur Fatimah; Guntur, Ahmad Ismail (SOSIORELIGIUS, 2025)
This study aims to examine how local cultural expressions are modified and capitalized through the live feature on the TikTok platform, and how this practice shapes a new form of creative economy in the digital era. The research employs a cultural anthropology approach through qualitative methods, including participatory observation and in-depth interviews with five content creators from regions with strong cultural backgrounds. The findings show that creators consciously package elements of culture, such as traditional dances, traditional clothing, and local languages, into formats that are engaging and easily accepted by a global audience. This process not only serves as a form of cultural preservation in the digital medium, but also generates significant economic profit for the creators. TikTok live proves to be a new space for negotiating identity and economy, where cultural expressions are commodified to attract attention and financial support from viewers. The conclusion of this study emphasizes that digital platforms, particularly TikTok, have created a new landscape for cultural and economic practices, where creativity and local heritage are converted into sources of income. This study contributes to the understanding of the relationship between culture, economy, and technology in the context of digital society.